PENGARUH KUALIFIKASI AKADEMIK, KOMPETENSI PEDAGOGIK TERHADAP KINERJA GURU IPS DI SMP NEGERI 1 SEPONTI - Sabandi Sabandi; Junaidi Junaidi; Warneri Warneri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2018)
AbstractThe aim of this research was describe (1) the influence of academic qualifications on the performance of IPS teachers in SMP Negeri 1 Seponti Kabupaten Kayong Utara; (2) the influence of pedagogic competence qualification on teacher performance of IPS in SMP Negeri 1 Seponti of Kayong Utara Regency; (3) the influence of academic qualification and pedagogic competence collectively on the performance of IPS teachers in SMP Negeri 1 Seponti Kabupaten Kayong Utara. The research method used is research method. The sample in this study. From the research results obtained (1) there is the influence of Academic qualifications on socail sciences teacher performance Seponti junior hight school 1 in Kayong Utara Regency amounted 43.50 percent. (2)  there is influence of pedagogic competence on socail sciences teacher performance Seponti junior hight school 1 in Kayong Utara Regency amounted to 54,40 percent; (3) academic qualification and pedagogic competence have simultaneous effect on socail sciences teacher performance Seponti junior hight school in Kayong Utara Regency amounted to 96,10 percent. Keyword: Academic  Qualifications, Pedagogic Competence, Teacher Performance